Fasting unmasks differential fat and muscle transcriptional regulation of metabolic gene sets in low versus normal birth weight men - Gillberg, Linn; Rönn, Tina; Jørgensen, Sine Wanda; Perfilyev, Alexander; Hjort, Line; Nilsson, Emma; Brøns, Charlotte; Vaag, Allan; Ling, Charlotte (EBioMedicine, 2019)
Individuals born with low birth weight (LBW) have an increased risk of metabolic diseases when exposed to diets rich in calories and fat but may respond to fasting in a metabolically preferential manner. We hypothesized that impaired foetal growth is associated with differential regulation of gene expression and epigenetics in metabolic tissues in response to fasting in young adulthood. Genome-wide expression and DNA methylation were analysed in subcutaneous adipose tissue (SAT) and skeletal muscle from LBW and normal birth weight (NBW) men after 36 h fasting and after an isocaloric control study using microarrays. Transcriptome analyses revealed that expression of genes involved in oxidative phosphorylation (OXPHOS) and other key metabolic pathways were lower in SAT from LBW vs NBW men after the control study, but paradoxically higher in LBW vs NBW men after 36 h fasting. Thus, fasting was associated with downregulated OXPHOS and metabolic gene sets in NBW men only. Likewise, in skeletal muscle only NBW men downregulated OXPHOS genes with fasting. Few epigenetic changes were observed in SAT and muscle between the groups. Our results provide insights into the molecular mechanisms in muscle and adipose tissue governing a differential metabolic response in subjects with impaired foetal growth when exposed to fasting in adulthood. The results support the concept of developmental programming of metabolic diseases including type 2 diabetes. The Swedish Research Council, the Danish Council for Strategic Research, the Novo Nordisk foundation, the Swedish Foundation for Strategic Research, The European Foundation for the Study of Diabetes, The EU 6th Framework EXGENESIS grant and Rigshospitalet.